18.9k views
5 votes
Let f(x) = 3x - 1 and g(x) = x^2 - 4.Find (f o g)(-1).

1 Answer

6 votes

Answer

(f o g) (-1) = -10

Step-by-step explanation

f(x) = 3x - 1

g(x) = x² - 4

We should note that (f o g) means that we try to work out f(x), but we will now replace the x with g(x)

(f o g) = f[g(x)]

(f o g) = 3[g(x)] - 1

= 3(x² - 4) - 1

= 3x² - 12 - 1

= 3x² - 13

And (f o g) (-1) means we substitute -1 for x in the simplified expression.

(f o g) (-1) = 3(-1)² - 13 = 3(1) - 13 = 3 - 13 = -10

Hope this Helps!!!

User DJViking
by
5.3k points